Identity and Sense Belonging of the Indonesian Jewish Communities - Utama, Mohamad Rezky (Nation State: Journal of International Studies, 2022)
Indonesian Jewish communities rarely appear in academic or scientific research. Some existing articles are about Jewish community in other countries or other minorities in Indonesia. This article is aimed to answer the question: “How is the identity and the sense of belonging of Indonesian Jewish Community, to Indonesia or to Israel? In this research, qualitative method is used to examine the issue. The approaches for this research are the concept of identity by Patricia Goff and Kevin Dunn and the Asabiyyah concept by Ibn Khaldun. The finding of this research is the fact that Indonesian Jewish community have a strong relationship and sense of belonging to Indonesia and identify themselves more as an Indonesian. Indonesian Jewish community had contributed to Indonesia’s nation building in the past during the participation of war of independence. And furthermore, with more understanding on the community, the community can take part in building the Indonesian nation in the future.